International encyclopedia of ergonomics and human factors - Karwowski, Waldemar (Boca Raton, FL : CRC/Taylor & Francis, 2006)
The book reviews applications, tools, and innovative concepts related to ergonomic research. Technical terms are defined (where possible) within entries as well as in a glossary. Students and professionals will find this format invaluable, whether they have ergonomics, engineering, computing, or psychology backgrounds. Experts and researchers will also find it an excellent source of information on areas beyond the range of their direct interests
Title from container
System requirements: Pentium II processor or higher; 32MB RAM; 360MB free hard disk dpace; 24x speed CD-ROM drive or faster; SVGAmonitor at 800x600, 256 colors; Windows 2000 or XP; Adobe Acrobat Reader 7; Internet explorer 5 or higher
Keywords: Human engineering -- Encyclopedias